Impact of warming and acidification on anxiety levels and camouflage abilities of cuttlefish early stages - Marques, Mélanie Alexandra Court (2021)
Tese de Mestrado, Ecologia Marinha, 2021, Universidade de Lisboa, Faculdade de Ciências